Dampak Interaksi Sosial Masyarakat Transmigran Sasak di Manggelewa Dompu NTB - Syarifuddin Syarifuddin; Dwi Setiawan Chaniago; Arif Nasrullah; Khalifatul Syuhada (Prodi Sosiologi Universitas Mataram, 2019)
This study examines the impact of social interactions of the Sasak transmigrants community in Dompu County Manggelewa. The release of transmigrants in this transmigration areacertainly has the process of adaptation and assimilation of both communities, both migrants and local communities. The method of research used is to use a qualitative approach. Datacollection is done through observation, in-depth interview (Indept interview) and FGD. FGD is used to complement the results of observation and interviews in depth. Data analysis is conducted through three phases of data reduction, classification and draw conclusions based on the overall data. The results of the research of local people and Sasak transmigrants have an equivalent interaction pattern, which tends to be associative. This can be seen from the social relations between Sasak migrant citizens with local people in various social activities that take place. Although between these two groups of people has a different social background that includes language, customs and political opportunities, they remain equal interactions. Assimilation and Acculturas are indicated by the habit of the two groups because it is vulnerable to a long time. The existence of Sasak migrant citizens in Manggelewa for a long time has made the two communities to adapt to each other. As in the event of a resident of Sasak migrant citizen with local people who choose to define newhabits. The habit formed is the unification of two or more assimilated cultures.